Алгоритм ймовірнісного висновку в байєсових мережах - Terentyev, O. M.; Bidiuk, P. I.; Korshevnyuk, L. O. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2009)
A novel algorithm for formation of probabilistic inference in Bayes networks on the basis of the training data, which is more exact and simple compared to conventional ones, is offered.